CONCORDANCIA DE LAS PRUEBAS DE ELISA Y HEMAGLUTINACIÓN INDIRECTA EN EL DIAGNÓSTICO DE LA TOXOPLASMOSIS PORCINA - Suárez A., Francisco (2002)
The study aimed to estimate the level of agreement between two serological diagnosis tests for toxoplasmosis in swine. The ELISA and the Indirect Hemagglutination Test were evaluated using blood sera collected in slaughterhouses from 303 pigs in Sao Paulo, Brazil and 93 pigs in Lima, Peru. The Kappa coefficient of agreement on the Brazilian sera was 26.0% and the confidence interval at 95% were 7.7 - 44.3% (P <0.05), whereas on the Peruvian sera was 36.6% and the confidence interval at 95% were 18.0 - 55.3% (P <0.01). Besides this, when considering the ELISA test as the reference test, the Indirect Hemagglutination Test had a co-positive reaction of 48.3% and a co-negative reaction of 86.5% in the Brazilian sera, and a co-positive reaction of 80.6% and a co-negative reaction of 61.3% in the Peruvian sera.